Peranan Terapi Awal dan Terapi Pemeliharaan pada Rapidly Progressive Periodontitis Type 1 - Anita H. Joedo (Faculty of Dentistry, Universitas Indonesia, 2015)
Rapidly Progressive Periodontitis (RPP) is a severe form of a periodontal disease which starts since a puberty age. The disease if a generalized periodontal destruction without a specific distribution mode: it develops more progressively but does not in accordance to local factors. The first step to the RPP treatment is initial therapy: i.e. DHE, scaling and root planing, and eliminating predisposing local factors and continued with a maintence therapy which will support the success of a surgery later. A study case: a 21-year old RPP woman showed hyperaemia, an abscess, a 10 mm mesial pocket depth, a 5 mm distal pocker depth, a 5 mm buccal pocket depth, a 2nd degree tooth mobility and a 3 mm buccal recession on 25. In the initial therapy she was given an amoxicillin, a metronidazole for killing a supra and subgingival baterial, vitamins B and C, and also a chlorhexidine 0.2% mouth wash for a week. After a week the abscess and the inflammation decreased, but the mobility was still in the same condition and the DHE was still evaluated because of the patient's social factor, the FO was delayed. The next visit was done every 2 monts for a year for maintenance care. The clinical result showed the gingival inflammation and the tooth mobility disappeared. Radiographically, the alveolar bone showed more radiopaque and the lamina dura was seen. In conclusio, the initial and the maintenance therapy was seen to heal the RPP.